2023
DOI: 10.3390/molecules28052187
|View full text |Cite
|
Sign up to set email alerts
|

Green Chemometric Determination of Cefotaxime Sodium in the Presence of Its Degradation Impurities Using Different Multivariate Data Processing Tools; GAPI and AGREE Greenness Evaluation

Abstract: Four eco-friendly, cost-effective, and fast stability-indicating UV-VIS spectrophotometric methods were validated for cefotaxime sodium (CFX) determination either in the presence of its acidic or alkaline degradation products. The applied methods used multivariate chemometry, namely, classical least square (CLS), principal component regression (PCR), partial least square (PLS), and genetic algorithm-partial least square (GA-PLS), to resolve the analytes’ spectral overlap. The spectral zone for the studied mixt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…1 The literature review revealed that several analytical approaches have been utilised in the determination of cefotaxime such as HPLC, UV-VIS spectrophotometric, potientiometry, electrophoresis and hydrophilic interaction chromatography. [2][3][4][5][6][7][8][9] Paracetamol (PAR); N-(4-Hydroxyphenyl) acetamide (Fig. 1) is related to a non-steroidal anti-inflammatory drugs (NSAIDs) which acts centrally and peripherally for treatment of non-inflammatory conditions.…”
Section: Introductionmentioning
confidence: 99%
“…1 The literature review revealed that several analytical approaches have been utilised in the determination of cefotaxime such as HPLC, UV-VIS spectrophotometric, potientiometry, electrophoresis and hydrophilic interaction chromatography. [2][3][4][5][6][7][8][9] Paracetamol (PAR); N-(4-Hydroxyphenyl) acetamide (Fig. 1) is related to a non-steroidal anti-inflammatory drugs (NSAIDs) which acts centrally and peripherally for treatment of non-inflammatory conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The consumption of dietary products might seem safe to the consumer, but it has been sometimes correlated with diseases such as liver injury [ 5 ]. In this regard, it is worth noting that variation in cultivation region, climatic conditions, type of the soil, containments in soil, water and air or even intentional adulteration can result in different impurities in the claimed plant products [ 6 , 7 , 8 , 9 , 10 , 11 ]. For instance, herbal cultivated in areas near industries or heavy traffics can accumulate toxic elements such as arsenic and lead [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the fact that some side components may greatly affect the safety and effectiveness of drugs. High-performance (HP) liquid chromatography (LC) with UV detection [ 1 , 2 ], reversed-phase HPLC with photodiode array [ 3 , 4 , 5 ], UV [ 6 , 7 ] or fluorescence [ 7 ] detectors, HP thin-layer chromatography with densitometry [ 1 , 2 , 4 ], capillary zone electrophoresis [ 8 , 9 , 10 ], and spectrophotometry combined with chemometrics [ 11 , 12 , 13 , 14 , 15 , 16 ] can be used to control the degradation and purity of drugs. At the same time, there are two main approaches to the analysis.…”
Section: Introductionmentioning
confidence: 99%
“…In the first case, active ingredients are determined in the presence of side components so that the content of the latter does not influence an analytical signal [ 1 , 2 , 3 , 8 , 11 , 12 ]. The second approach is the simultaneous determination of drug components, including related organic impurities and degradation products [ 4 , 5 , 6 , 7 , 9 , 10 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%